A comparative study of fat transfer with compression therapy versus compression therapy alone in the treatment of hypertrophic burn scars: A prospective randomized trial - Ravi Saroha; Vijay Langer; S K Singh (Wolters Kluwer Medknow Publications, 2022)
Introduction: Hypertrophic scars (HS) remain the main cosmetic concern after complete healing of burns for both patients and treating burn surgeons. HS are managed conservatively using compression therapy, but in our study, we attempt fat grafting with compression therapy to identify which treatment modality leads to better outcomes in patients. Materials and Methods: A total of 84 patients (42 in each arm) in this prospective single-blind randomized controlled study had undergone fat transfer with compression therapy and compression therapy alone at a tertiary care burn center for treatment of HS from July 2015 to June 2017. Results: Out of the total of 84 patients, 54 were male and 30 were female with the mean age being 26.19 and 37.93 years in the case (test) and control group, respectively. Among them, 54 were flame burns and 20 were electrical burns. Mean total body surface area of 23.67% and 44.36% in the case and control, respectively, represents the extent of burns in majority of patients. Assessment of scars was done using the Patient and Observer Scar Assessment Scale which was found statistically significant (<0.005) in both patient and observer assessment in case group, i.e., fat grafting with compression therapy at all times during follow-up. Early complications in form of erythema and swelling in 20 cases, swelling in 13, erythema in 4, and none in 5. Conclusion: Our study suggested the superiority of fat grafting with compression therapy in the improvement of HS. Patients tolerated outpatient procedures well with minimal morbidity and self-limiting complications.